Daily tea drinking is not associated with newly diagnosed non-alcoholic fatty liver disease in Chinese adults: the Tianjin chronic low-grade systemic inflammation and health cohort study - Yang Xia (Nutrition Journal, 2019)
Abstract Background Previous studies have reported that tea extract supplementation has potential benefits on the risk factors of non-alcoholic fatty liver disease (NAFLD); however, no study has investigated the direct effect of daily tea consumption on the prevalence of NAFLD in the general population. This cross-sectional study aimed to evaluate the associations between tea consumption and the prevalence of newly diagnosed NAFLD among Chinese adults. Methods The present cross-sectional study was based on the Tianjin Chronic Low-grade Systemic Inflammation and Health Cohort Study. In total, 19,350 participants were enrolled in the analyses. Tea consumption was assessed via a self-administered food frequency questionnaire. NAFLD was diagnosed via liver ultrasonography and no history of heavy alcohol intake. Logistic regression analysis was used to estimate the associations between tea consumption and the prevalence of NAFLD. Results Consumption of green tea, oolong tea, and black tea were positively associated with the prevalence of newly diagnosed NAFLD before adjustments. Compared with the participants who never drink tea, the odds ratios (95% confidence interval) of newly diagnosed NAFLD in the highest categories (≥ 1 cup/day) of green tea, oolong tea, black tea, and jasmine tea were 1.48 (1.33, 1.65), 1.50 (1.33, 1.68), and 1.28 (1.13, 1.46), and 1.36 (1.20, 1.54) before adjustments, respectively. However, no significant association was found between tea consumption and the prevalence of NAFLD after adjusting for socio-demographic, behavioural, anthropometric, dietary, and clinical confounding factors. Conclusion There is no significant association between daily tea drinking and newly-diagnosed NAFLD in general Chinese adults.